A combination of pain indices based on momentary assessments can predict placebo response in patients with fibromyalgia syndrome. Issue 2 (February 2021) - Obbarius, Alexander; Schneider, Stefan; Stone, Arthur A.
Abstract : Abstract: Many factors are known to affect assay sensitivity; however, limited attention has been devoted to understanding whether characteristics of patients' baseline pain impact assay sensitivity. In this study, we tested whether a combination of 3 baseline pain indices based on ecological momentary assessments (EMA) could detect patients with enhanced responses to placebo. The analysis was conducted with secondary data from 2 clinical trials in fibromyalgia patients (N = 2084). For each patient, pain intensity, pain variability (individual SD), and pain consistency (first-order autocorrelation) were computed from baseline EMA. A latent profile analysis identified 3 subgroups of patients based on these indices. Group 1 (n = 857, 41.3%) showed the lowest pain intensity levels, coupled with the highest consistency and greatest variability of pain. Group 3 (n = 110, 5.3%) showed the opposite pattern, and group 2 (n = 1109, 53.4%) showed intermediate levels on all pain indices. It was then tested whether the subgroups moderated treatment effects (changes in pain for active treatment vs placebo) using repeated-measures analysis of variance. Treatment effects varied significantly between subgroups. Patients in group 3 demonstrated greater reduction in pain in response to placebo then those in groups 1 and 2. Further analysis showed that the removal of patients in class 3 would significantly enhance the observed treatment effect by 8% to 15%. In conclusion, profiles of pain characteristics derived from baseline EMA may be useful for detecting patient subgroups with enhanced placebo responses that can diminish assay sensitivity in pain clinical trials. Abstract : Supplemental Digital Content is Available in the Text.A small group of fibromyalgia patients with a combination of high pain levels, low variability, and low consistency were found to have an above-average response to placebo, thus reducing assay sensitivity.